Comprehensive Review of Nocturnal Enuresis in Children - Mehrdad Sarabi; Niloufar Nikpasand; Elnaz Mahmoudabadi; Ashkan Torshizian; Alireza Ghodsi; Anoush Azarfar (Mazandaran University of Medical Sciences, 2022)
Background: Enuresis is a common problem that affects up to 15% of 5‐year‐old children and may have significant psychological, emotional, and social consequences for both the child and their family. Enuresis is the inability of toilet‐trained children to hold urine during the night. It can be classified as primary and secondary. Secondary enuresis occurs in children who have had a dry duration of more than six months; otherwise, it is called primary enuresis. Objectives: This narrative review aims to summarize the available data on the epidemiology, etiology, pathophysiology, evaluation, and treatment of children with enuresis. Methods: This study was conducted through a literature search with the keywords based on Medical Subject Headings (MESH) and were combined with other keywords, including enuresis, pediatric, incontinence, and treatment using PubMed, Embase, Web of Sciences, Scopus, and Cochrane databases. Results: The initial evaluation of enuresis needs a detailed medical history and a careful physical examination with no need for radiology and invasive procedures. The treatment's mainstay is non‐pharmacological treatments, such as behavioral intervention followed by pharmacotherapy. The appropriate treatment chosen depends on the children's age, midnight voiding patterns, and family and child preferences. Conclusions: Enuresis is a common disorder that affects both the child and the family in many ways. Enuresis's etiology is complex, and it is still not well understood. The child and family must be included in the treatment process, and potential pathophysiological causes must be taken into account.